PEER COUNSELING ANTI BULLYING UNTUK MENINGKATKAN KESEHATAN MENTAL - Itto Nesyia Nasution; Nurul Aiyuda; Khairunnisa Syarif; Mieke Irmades Aurel; Dimas Agiel Fachriandi (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
In recent years, bullying cases have been quite concerning. Bullying or bullying is very threatening to the mental state of children. Bullying is a repetitive negative behavior that is carried out consciously, usually carried out by a person or group of people who have more power than the victim. For this reason, it is important for educational institutions to prepare or design Peer Counseling training for their students to support students' mental quality and minimize bullying problems that arise among school youth. This program was carried out using the TOT (training of trainer) method with a total of 15 peer counselors. The scales used are the empathic listening and Mental Health scales. The implications of this program can be used as a reference and understanding for female students in efforts to prevent and minimize cases of bullying that occur among school students. By conducting peer counseling training and mental health seminars with the theme of bullying at school, students can actively practice what they have learned from the service program in the hope of being able to help the performance of guidance and counseling teachers at school.